Strategy for the Development of Agrotechnology and Sustainable Horticultural Vegetable Agribusiness Areas Based on Leading Commodities in Tomohon City - Wariki (Jurnal Agroekoteknologi Terapan, 2025)
Vegetable development in Tomohon City consists of carrots, cabbage, mustard greens, cauliflower, spring onions, cayenne pepper and tomatoes. Based on data from 2019 to 2021, the largest planting area and production were for carrots and cabbage commodities. The planting area and production of vegetables from 2018 to 2021 decreased, in 2018 reaching 350 and 625 ha with a productivity of 28,000 kg/ha and 22,000 kg/ha. In 2021, the area of ​​carrots and cabbage reached 300 ha and 425 ha respectively with a production of 25,000 kg/ha and 20,000 kg/ha (Tomohon City Agriculture Service, 2022). The obstacles to the reduction in planting area and production in 2020-2021 were possible due to the COVID-19 pandemic which caused a decrease in people’s purchasing power, reduced availability of labor, increased pesticide prices, and increased fertilizer prices. During the COVID-19 pandemic, the selling price of vegetables increased, but the amount of production decreased drastically, which caused farmers’ income to decrease. The purpose of the study was to determine the superior vegetable commodities in Tomohon City, analyze priority factors and find strategies for developing sustainable superior vegetables in Tomohon City. Data collection from May to July 2024 and reporting in August to October 2024. The location of the study was in Tomohon City, at coordinates LU 10.191 - 10.281 and BT 10.18’.51’’- 1240.49’.40’’ (BPS, Tomohon in Figures, 2022). Respondents were taken by purposive sampling with a total of 15 respondents, consisting of 3 decision-making officials, namely the Head of the Agriculture Service, the Head of the Food Service and the Head of the Environmental Service. In 2 experts, namely environmental experts and economists and in 10 farmers. The research variables consist of internal and external factors. The analysis method consists of basic commodity analysis, Shift Share Analysis (SSA) analysis, Delphi analysis, Analytical Network Process (ANP), SWOT analysis and Quantitative Strategic Priority Management (QSPM) analysis. The results of the study showed that the priority factors in the development of Sustainable Vegetable Horticulture Agribusiness Areas in Tomohon City consisted of land conditions, high prices, productivity, low capital, limited labor, limited production facilities, out-of-town marketing, local marketing, government programs, out-of-town products, product damage and pests and diseases. The priority superior commodities in the development of Sustainable Vegetable Horticulture Agribusiness Areas in Tomohon City consisted of the first priority of carrots, the second priority of mustard greens and the third priority of cabbage. Development Strategy with priority stages of increasing production, increasing marketing, increasing quality, government assistance, organic fertilizer, crop rotation, capital loans and pest and disease control. Keywords: Strategy, Area, Horticulture, Vegetables, Sustainable